2016
DOI: 10.7717/peerj.2119
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microRNA, gene expression and transcription factors signature in papillary thyroid cancer with lymph node metastasis

Abstract: Background. Papillary thyroid carcinoma (PTC) is the commonest thyroid malignancy originating from the follicle cells in the thyroid. Despite a good overall prognosis, certain high-risk cases as in those with lymph node metastasis (LNM) have progressive disease and poorer prognosis. MicroRNAs are a class of non-protein-coding, 19–24 nucleotides single-stranded RNAs which regulate gene expression and these molecules have been shown to play a role in LNM. The integrated analysis of miRNAs and gene expression pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…Manuscript to be reviewed translational inhibition (Ab Mutalib et al 2016;Bartel 2009;Yang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuscript to be reviewed translational inhibition (Ab Mutalib et al 2016;Bartel 2009;Yang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed uncover the regulatory mechanism of mandibular MSCs. miRNAs function by base pairing to complementary sites in the 3' untranslated region (3'UTR) of mRNAs (Ab Mutalib et al 2016;Bartel 2009). The connections between miRNAs and the cell lineage commitment of MSCs have been demonstrated by several studies using BMMSCs from femurs (Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miRNA expression-based prognostic signatures, which were identified by Cox proportional regression models in cancer prognosis prediction using TCGA datasets, have been developed in multiple cancers, such as pancreatic cancer, 26 , 27 stomach adenocarcinoma, 28 head and neck squamous cell carcinoma, 29 , 30 gliomas, 31 glioblastoma, 32 34 cervical cancer, 35 bladder cancer, 36 breast cancer, 37 , 38 colon cancer, 39 lung cancer, 40 , 41 and HCC. 42 44 In addition, diagnostic 45 47 and metastasis 48 related miRNA signature biomarkers have been investigated in multiple cancers using TCGA datasets. Updates in the TCGA HCC dataset and the miRNA expression-based prognostic signatures require comprehensive survival analysis to validate; therefore, further investigations of miRNA expression prognostic signatures with a reliable method and comprehensive evaluation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…There are two miRNAs that are involved in both comparison groups, namely, hsa-miR-7-5p and hsa-miR-181b-5p, hence suggesting that both miRNAs are involved in the pathogenesis of PTC in general and are not specific to LNM. Various studies have reported that hsa-miR-7-5p has a low expression level in PTC samples ( 13 , 31 , 50 ). Hsa-miR-7 plays a role in regulating cell growth, migration, and invasion by targeting PAK1 in thyroid cancer ( 51 ).…”
Section: Discussionmentioning
confidence: 99%